"She's just a bad mother": Perceptions of failure to protect children in relationships with intimate partner violence. Issue 4 (1st November 2020) - Kelton, Katherine; Elrod, Noel; Kaylor, Leah; Copeland, Melissa; Weaver, Terri L.
Abstract: Failure to Protect (FTP) is a legal statute that connotes permitting or enabling child abuse by a parent or guardian. Women are more likely than men to be charged for 'failing to protect' children from exposure to intimate partner violence or physical abuse. Factors hypothesized to be associated with disparities in charges of FTP were examined. Participants ( N  = 375) recruited from Amazon's Mechanical Turk (MTurk) were randomized to read one of two vignettes of an FTP case, with the gender of the non-offending parent manipulated. Study participants rated the non-offending parent in terms of guilt (yes/no) for FTP. Women were more likely to be found guilty of FTP than men, and victim-blaming attitudes and gendered parenting expectations influenced verdicts.